Research Projects Portfolio.,Analysing Social Research Traditions: A Study of the Paper: Young Adolescents ' Perceptions of Environmental Issues,Situational Analysis of the Albany Working for Water Project,Perceptions of Work-Related Environmental Issues among Albany Working for Water Workers: Educational Implications,Drama as a Process for Adult Education in the Workplace: A Case Study of the Albany Working for Water Project - Schudel, Ingrid Joan (Rhodes University, Faculty of Education, Department of Education, 2000)
This collection of research projects tells a story of the time I have spent with members of the Albany Working for Water team; including preparations made, lessons learned and insights gained. My first project was to analyse the methodology of a research paper. I chose the paper by Arjen Wals because I intended, like him, to examine people's perceptions of environmental issues. From this paper I gained ideas for a qualitative research process and learnt the importance of theoretical and methodological consistency. My next project was to present a report on my research into the perceptions of workrelated environmental issues among the Albany Working for Water workers. From this research I gained insight into the knowledge of the workers and also some of the misconceptions that they have about social and ecological issues. I made educational recommendations based on these insights. This experience inspired me to initiate a play with a group of the workers about alien plant eradication. The process of developing this play formed the basis for a research paper that I have submitted as another research project. Concurrent with the development of the play, I conducted a fourth research project that was a situational analysis of the Albany Workingfor Water Project. I hoped that this analysis would provide useful insight into the context of the above two projects. Overall, I hope the story reflects how I have grown through the learning experiences I shared with the Albany Working for Water team. I would like to extend to my thanks to all those who assisted and shared my journey with me.
Keywords: Environmental education -- South Africa -- Eastern Cape